Relationship Between Organizational Commitment and Job Satisfaction Among Employees - Aniss Yusairah, Abdul Kadir (2011)
The purpose of this study is to examine the relationship between components of organizational commitment and job satisfaction among employee in private sector. Therefore this study could make important contribution to extant research in management and organizational behavior. In the beginning of this study, the purpose, research question, and the need for the study is given. Then, literature is discussed about organizational commitment and job satisfaction that focusing on the relationship between them. The study generated a 100 percent response rate from 125 respondents. The result from Multiple Regression Analysis showed that affective commitment have significant positive relationship with job satisfaction. However, continuance and normative commitment have no significant relations with job satisfaction. The overall model or the coefficient determination was quite high, R Square of 40.5%